Plasticizing poly(lactic acid) using epoxidized palm oil for environmental friendly packaging material = Peningkatan fleksibiliti poli(laktik asid) menggunakan minyak kelapa sawit terepoksi untuk aplikasi pembungkus mesra alam - Ali, Fathilah; Jama Awale, Raina; Fakhruldin, Hanan; Anuar, Hazleen (The Malaysian Analytical Sciences Society, 2016)
Petrochemical based polymers used in packaging materials are causing various environmental problems. Therefore, biopolymers prepared from renewable sources have high potential to substitute the commercially available non-degradable polymer. Poly(lactic acid) (PLA) is one of the biodegradable polymers that can be used to substitute in the application of petrochemicalbased polymers. Environmental friendly and biodegradable epoxidized palm oil (EPO) was used as plasticizer in this study and it was incorporated into PLA matrix through solution blending method. The mechanical properties were determined through three-point flexural test and tensile test. Tensile results revealed that the flexibility of PLA can be improved by the addition of epoxidized palm oil (EPO) as plasticizer in the polymer. PLA/EPO blend at ratio 100:10 showed significant flexibility among the other PLA/EPO blends. The thermal properties of neat PLA and PLA/EPO blends were characterized by using Differential Scanning Calorimetry (DSC). The glass transition temperature (Tg) decreased by addition of plasticizer, indicated the chain mobility of PLA increased in the PLA/EPO blends system. The improved flexibility of PLA by using EPO as plasticizer showed that it has high potential to be used as environmental-friendly packaging material.